DAYA SAING EKSPOR DAN PERKEMBANGAN PANGSA PASAR IKAN TUNA INDONESIA DI PASAR INTERNASIONAL PERIODE 2012-2016 - Dwi Ayu Sekarini Putri; Firman Rosjadi; Made Siti Sundari (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
This study seeks to understand the competitiveness of the Indonesia tuna fish by comparing with other Asian countries. The analysis employed the Revealed Comparative Advantage (RCA) method to examine the Indonesian tuna fish exportvalue data in comparison to the total export value of all commodities in Indonesia. The observation took place between 2012 and 2016. The findings indicates that there was an increasing amount of tuna fish volume before 2014, followed by the plumeted amount of export at the following years. However, the RCA index remained greater than one, which indicates that the Indonesian tuna still became the major export product. The highest RCA Index occuredd in 2013 with 4.72 for 4,63% of Indonesia’s market share value. This study also discuss some limitations of the applied RCA.